Usaha peningkatan pengetahuan metode pengelolaan sampah bagi santri Balai Pengajian Babussalam Gampong Limpok, Aceh Besar (Efforts to improve knowledge of waste management methods for students of the Quranic Recitation Hall Babussalam Limpok Village, Aceh Besar District) - Ali, Nurdin; Arhami, A; Ali, Masri; Thalib, Sulaiman (Universitas Syiah Kuala, 2021)
The purpose of this community service activity is to provide education on waste management to the students of the Quranic Recitation Hall Babussalam, Limpok Village. This community service activity was attended by 20 students, consisting of groups of primary and junior high schools, divided into two stages, namely: making the rubbish bin and counseling on waste management at the Quranic Recitation Hall Babussalam. The counseling and socialization were carried out by direct introduction to students and by providing waste collection facilities according to the types of waste. The results of this community service activity can be declared successful as seen from their seriousness in listening to the presentation of the material, responding spontaneously, and discussing seriously during the activity. They can understand the benefits of solid waste management and are proven to be able to mention the negative and positive effects of waste. Garbage can be an income if it is sorted out and a disaster if it is disposed of in any place according to them and an agent of change, especially in the environment where they live and the Limpok Village community in general. In conclusion, all participants had a good understanding of the introduction to waste processing methods, types of organic and inorganic waste, and residues which were marked by the ability of each participant to answer questions given by the service team.